Coasting-cruising Combined Control Strategy Based on Train Energy-efficient Operation - GAO Hao; CHAI Juan; LING Xiaoque; XU Haigui (Chengshi guidao jiaotong yanjiu)
Objective Current train operation control system incorporates an automatic driving subsystem, enabling train cruising control. To further reduce train operational energy consumption while maintaining service quality, it is necessary to develop a coasting-cruising combined control strategy based on the existing train operation control strategies. Method Building on existing train operation control strategies, the research approach for the coasting-cruising combined control strategy is introduced. Based on Simulink simulation software, a train energy-efficient driving optimization model is constructed. The optimization objectives are set to minimize train operational energy consumption and ensure punctual operation by introducing weight factors to normalize the dual-optimization goal. Multiple control stages are divided according to the line conditions, with maximum traction, coasting, cruising, and maximum braking as control inputs for each stage. The genetic algorithm is used to calculate respectively the train energy-efficient optimized operation curves under the coasting-cruising combined control strategy and the multiple coasting control strategy. Result & Conclusion In long uphill sections, the coasting-cruising combined control strategy demonstrates better energy-saving effects compared to the multiple coasting control strategy. But in long downhill sections, there is no significant difference in energy-saving optimization effects between the two control strategies. When maintaining the same target running time and optimizing for different target energy consumptions multiple times, it is found that the coasting-cruising combined control strategy could achieve better energy-saving effects with higher optimization stability.